1990
DOI: 10.1159/000213199
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Amylase Activity of the Aged

Abstract: Previous studies from America and Japan have reported that salivary amylase activity was reduced in the elderly. In contrast to these studies, a recent Chinese study reported an increase in salivary amylase activity in the aged. Our study examined approximately equal numbers of Chinese and non-Chinese Americans. The concentration of salivary amylase was estimated from the activity obtained with a colormetric coupled assay utilizing 4NP-G7. Activity was found to be increased in the aged. Our data are discussed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…The concentration and activity of salivary amylase, an enzyme involved in the initiation of polysaccharide digestion and the modulation of immunity, can be altered by mental health, 14 body composition, diet, 15 and age. 16 The present study has shown that it can also be affected by physical conditioning, even in elderly individuals: EA showed an increase of 130% at the time of exhaustion, with a subsequent reduction thereafter. By contrast, PAE showed a 68% increase in the time to exhaustion with a later peak (T5), reaching an elevation of 100%, and a subsequent sudden reduction.…”
Section: Discussionsupporting
confidence: 49%
“…The concentration and activity of salivary amylase, an enzyme involved in the initiation of polysaccharide digestion and the modulation of immunity, can be altered by mental health, 14 body composition, diet, 15 and age. 16 The present study has shown that it can also be affected by physical conditioning, even in elderly individuals: EA showed an increase of 130% at the time of exhaustion, with a subsequent reduction thereafter. By contrast, PAE showed a 68% increase in the time to exhaustion with a later peak (T5), reaching an elevation of 100%, and a subsequent sudden reduction.…”
Section: Discussionsupporting
confidence: 49%
“…Ben‐Aryeh et al () reported a decline in amylase activity of unstimulated and stimulated parotid saliva with age, while Aguirre, Levine, Cohen, and Tabak () did not find differences in α‐amylase concentration in stimulated parotid saliva of individuals aged 23–84 years. Wang and Woolfolk () investigated age‐related changes in salivary amylase activity between young (<51 years) and elderly (>60 years) Chinese and non‐Chinese Americans. Enzyme activity increased with age in both groups, but this age effect was more pronounced in the Chinese group.…”
Section: Discussionmentioning
confidence: 99%
“…Even though it is known that perception and preference vary greatly among these consumer groups, differences and similarities in oral physiology, and saliva composition between Westerns and Asians have not yet been described. Wang and Woolfolk () investigated age‐related changes in salivary amylase activity of Chinese and non‐Chinese Americans. The authors observed a more pronounced increase in enzyme activity with age in the Chinese group.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, older non-fed Asian elephants showed higher sAA activity independent from season in contrast to African elephants where age was not correlated with activities of any of the enzymes. Increasing sAA activity with age was already shown in human saliva, which was speculatively caused by age-related histological changes in acinar and ductal cells (Ben-Aryeh et al 1990 ; Wang and Woolfolk 1990 ).…”
Section: Discussionmentioning
confidence: 91%